Stripes by Example - Watson, Brent (Springer, 2015)
In this 100-page book, you will find that Stripes provides a very simple learning path, where you do not need to understand the entire framework in order to use it. The concept of this book is exactly that – to get you using the framework and writing code immediately. You will be off and running in no time, and adding to your skill set as we progress. This book is written with exactly that learning method in mind. No filler, no empty explanations... just code. You won't be driving solo, however. Each code example is heavily annotated with comments and tips, so that you not only understand each snippet, but can also dive deeper if you so choose.